Lecciones del pasado literario grecorromano sobre la paz (2021)
This article analyzes the literary contributions that have been made from the Greco-Roman world in relation to the different ways of conceiving the peace. The above in order to find analogies, differences and ways of conceiving processes of violence and peaceful understanding between the parties in conflict from events that occurred in societies such as Colombia, where peace has been seen at various prolonged moments of its absent existence of the feeling of the people.